Defining domain-specific object-oriented modeling languages as UML profiles - Grant, Emanuel Sylvester, author; France, Robert B., advisor; Bieman, James M., committee member; Turk, Daniel E., committee member; Florant, Gregory L., committee member (Colorado State University. Libraries, 2002)
The use of general purpose modeling languages (GPMLs) in specifying software applications is giving way to the increasing usage of domain-specific modeling languages (DSMLs). DSMLs offer a vocabulary of terms and concepts that are fundamental to the problem and solution domains, whereas GPMLs constructs are usually too generic to be directly applied in some domains. The Unified Modeling Language (UML) is a comprehensive set of graphical and textual notations for modeling various views of software systems, using object - oriented concepts. Though the UML has been designed to satisfy the requirements of the typical software modeling tasks, there are some projects that require features beyond those explicitly defined in the UML. Application of the UML extension mechanisms on a coherent set of UML metamodels. which are defined by the requirement of a specific application domain or enterprise, results in what is termed a UML profile. Profiles may be used to package domain-specific modeling entities that are applied in building application models for the domain. The objective of this research is to develop domain-specific object-oriented modeling languages that are defined in the format of UML profiles. Most DSMLs may be viewed as high level programming languages, because they are usually applied near the end of the design phase of application development and are generally textual models. DSML, as used in this work, are graphical in presentation, and are intended to be used at the analysis and design stages of application development. The result of this work will be the definition of components of DSMLs that constitute the syntax and semantics of the language, and the formulation of a process for defining DSMLs in the format of UML profiles. The main benefits that are realized from using DSML are the reuse of standardized domain artifacts, reduction in the time to deliver complete products, and more easily maintained applications.
Keywords: computer science